An Elaborate Review for Micro-Fin Heat Sink - Ibtisam A. Hasan; Sahar R. Fafraj; Israa A. Mohmma (Engineering and Technology Journal, 2020)
Heat sinks are low cost, the process of manufacturing reliability, and design simplicity which leads to taking into consideration various cutting-edge applications for heat transfer. Like stationary, fuel cells, automotive electronic devices also PV panels cooling and other various applications to improve the heat sinks thermal performance. The aim is to focus on some countless fundamental issues in domains such as; mechanics of fluids and heat transfer, sophisticated prediction for temperature distribution, high heat flux removal, and thermal resistance reduction. The outcome of this survey concluded that the best configuration of heat sinks has a thermal resistance about (0.140 K/W to 0.250 K/W) along with a drop of pressure less than (90.0 KPa) with a temperature gradient about 2 °C/mm. Heat sinks with square pin fins lead to enhance the effectiveness of heat dissipation than heat sinks with microcolumn pin fins. While other researches recommend the use of high conductive coating contains nano-particles. The present survey focuses on the researches about future heat sink with micro fin and the development to resolve the fundamental issues. The main benefits and boundaries of micro fins heat sink briefed.